1990
DOI: 10.1073/pnas.87.19.7678
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta stimulates mammary adenocarcinoma cell invasion and metastatic potential.

Abstract: The experimental metastatic potential of 13762NF mammary adenocarcinoma clone MTLn3 was tested after pretreatment in serum-free medium containing transforming growth factor (TGF) 8,1 at 0-5000 pg/ml. Lung colonies were measured 2 weeks after inoculation in syngeneic F344 rats, and a bell-shaped dose-response curve with 2-to 3-fold increase in number of surface lung metastases was seen. Maximal enhancement occurred at the 50 pg/ml dose level. The effect was specific because addition of neutralizing anti-TGF-18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
180
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(191 citation statements)
references
References 32 publications
8
180
1
2
Order By: Relevance
“…39,40 In addition to its contribution to epithelial homeostasis and development, TGF-␤ plays a role in tumor invasion and metastasis. [41][42][43] Conceivably, this might occur through modulation of laminin-5 expression, though we have not tested this hypothesis directly. Arguing against this is the fact that BICR16 and DOK cells, which express contrasting levels of ␥2 mRNA, remain responsive to the antiproliferative effects of TGF-␤.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 In addition to its contribution to epithelial homeostasis and development, TGF-␤ plays a role in tumor invasion and metastasis. [41][42][43] Conceivably, this might occur through modulation of laminin-5 expression, though we have not tested this hypothesis directly. Arguing against this is the fact that BICR16 and DOK cells, which express contrasting levels of ␥2 mRNA, remain responsive to the antiproliferative effects of TGF-␤.…”
Section: Discussionmentioning
confidence: 99%
“…shown to stimulate tumour cell invasion in vivo and metastatic potential in vitro (Welch et al, 1990). In order to investigate the contribution of different cell types to protein levels in the tissue, we cultured human primary bladder cells separating epithelial from fibroblast cells by different culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The transforming potential of TGF-b was rediscovered when it was shown that pretreatment of adenocarcinoma cells with TGF-b1 in vitro enhanced their metastatic ability when injected into syngeneic rats (Welch et al, 1990). Numerous studies have demonstrated that TGF-b1 can drive malignant progression by its pleiotropic effects on tumor cells (invasion and metastatic spread) and their microenvironment (angiogenesis and immunosuppression) (Massague´et al, 2000).…”
Section: Introductionmentioning
confidence: 99%